PENGARUH DIGITAL MARKETING TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN KE KEBUN RAYA BOGOR - Samuel; Wildan Rizky Rahadian; Nisa Rahmaniyah Utami (Bogor Hospitality Journal, 2022)
The purpose of this study was to determine the effect of digital marketing on the decision to visit the Bogor Botanical Gardens. This study uses a quantitative approach and data analysis methods in this study using simple linear regression using SPSS 16.0, to see how much influence digital marketing has on visiting decisions. The sampling technique used in this research is purposive sampling. The number of samples studied in this study were 100 respondents who had visited the Bogor Botanical Gardens. The results of the study prove that there is a positive and significant effect with a significance level (Sig.) of 0.00, which is below 0.05. This analysis finds that there is an influence between Digital Marketing on Visiting Decisions.